Growing explanations : historical perspectives on recent science - Wise, M. Norton (Science and cultural theory., 2004)
Written by leading historians and philosophers of science, these essays examine the range of subjects, people and goals involved in changing the character of scientific analysis over the last several decades and highlights the alternatives that new fields offer to the re-ordering of knowledge to emphasize growth, change and contingency.